Early Stimulation and Nutrition: The Impacts of a Scalable Intervention (2018)
This paper evaluates the effects of the implementation of a structured early stimulation curriculum combined with a nutritional intervention through public large-scale parenting support services for vulnerable families in rural Colombia, known as FAMI, using a clustered randomized controlled trial. We randomly assigned 87 towns in rural areas to treatment and control and 1,460 children younger than 1 year of age were assessed at baseline. The interventions were also complemented with training, supervision and coaching of FAMI program facilitators. We assessed program effects on children¿s nutritional status, and on cognitive and socio-emotional development; as well as on parental practices. The interventions had a positive and significant effect on a cognitive development factor based on the Bayley-III of 0.15 standard deviations. We also report a reduction of 5.8 percentage points in the fraction of children whose height-for-age is below -1 standard deviation. We do not find any effects on socio-emotional development. We report positive and statistically significant effects on the quality of the home environment (0.34 SD).